Cities Through the Ages: One Thing or Many? - Smith, Michael E.; Lobo, José (Frontiers in Digital Humanities, 2019)
The variability among cities, from the ancient world to the present, can be organized usefully in two ways. First, a focus on the dominant urban activities and processes leads to the recognition of two basic urban types: economic cities and political cities. Most cities today are economic cities in which growth proceeds through agglomeration processes. By contrast, most cities in the ancient world (and some today) are political cities, in which power and administration play a major role in structuring cities and generating change. Second, an alternative focus on processes of social interaction within the urban built environment leads to the recognition that there is only one kind of settlement that includes all cities—economic and political; past and present. Cities in this sense are settings for “energized crowding.” Processes of interaction generate both economic and political growth, and they produce and influence the built forms and social characteristics of all cities. Our model helps scholars distinguish the unique from the universal traits of cities today and in the past.